PENGUATAN GIZI DAN IMUNITAS UNTUK MAHASISWA MANAJEMEN UNESA YANG TERDAMPAK PANDEMI COVID 19 - Khoirur Rozaq; R.A Sista Paramita; Fandi Fatoni (Jurnal Abdi Masyarakat (JAM), 2021)
Surabaya is the area with the highest spread of the Covid 19 virus in East Java. Every day more people infected with this virus in the city of Surabaya. With the high number of the spread of the Covid 19 virus, the Surabaya city government and the East Java provincial government imposed large-scale social restrictions (PSBB) to break the chain of spreading the virus. In addition, nationally, the minister of national education, with the COVID-19 pandemic, issued regulations for learning from home for schools from elementary to high school and university. The problem arises when learning activities from home for students who are in a boarding house because it is affected economically, socially and psychologically. There are those who cannot go home because of PSBB regulations, they are afraid that their home area will be in the red zone and various other reasons that require them to stay in the boarding house. This community service has a target of increasing nutritional resilience and immunity, especially to ward off disease and maintain body immunity so that it remains excellent for students who survive at the boarding house. The method used was data collection of students affected by Covid 19 who survived in the boarding houses around the Ketintang UNESA campus and the distribution of nutrition and immunity enhancing food ingredients. As a result, there were 35 packages distributed to Unesa FE management students who were affected by Covid 19 to survive at home until now. The recipient of the package considers that the package is very important to maintain endurance so that it is not susceptible to disease. Keywords: Strengthening nutrition, immunity, management students, covid 19